NGAJI BANDONGAN: TAFSĪR JALĀLYN GUS BAHA STUDY AS A PARADIGM OF ONLINE ACCULTURATION OF TURATS AND SOCIAL MEDIA - Aishah Khoirunnisa; Atabik, Ahmad (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
This research presents a new view of online acculturation, namely ngaji bandongan, which focuses on studying Gus Baha tafsīr jalalyn on the YouTube platform in reviewing the NU tafsīr account. A field study guides this analysis by looking at the current acculturation in social media, where ngaji bandongan is a permanent tradition in studying the yellow book. This research uses a qualitative methodology using ethnography to describe and build the social culture of a society. The theory used to analyze this is the theory of cultural acculturation, which, in this case, is ngaji bandongan. The data comes from a literature review, document study, and in-depth observation. The results in this analysis are in several aspects, namely the way of delivery of Gus Baha who uses language that is easy to understand and humorous, making it attractive to the younger generation. The content of Gus Baha's tafsīr Jalālyn study is a new paradigm in a tradition adapted to digital platforms to reach a wider audience, especially the younger generation. This shows that turrets remain relevant and contextual in the digital age.